Strategy and facilitating model for small scale terasi business in the Camar Laut small enterprises. Issue 1 (February 2021) - Humairani, R; Akmal, Y; Muliari,; Maritalia, D; Yunizar, Z; Mangkuwinata, S; Muttaqim, H; Zulfahmi, I
Abstract: The development of small and medium-sized enterprises (SMEs) needs to be carried out considering their significant role in the economic growth of a region. The efforts of the development of SMEs can be done by improving business management followed by arrangement business legality. Business legality is an important factor, especially for SMEs involved in food production which has an important role in food safety assurance for consumers. Business legality will simplify market access to expanding distribution and increasing demand for products. The aim of the development business legality guidance and facilitating it is to assist Camar Laut small enterprises involved in the shrimp paste processing industry to obtaining business legality and ensuring that production aspects are carried out properly resulting in continuity of business legality. The activities performed an increase in understanding, skills, and turn over of human resources in Camar Laut small enterprises.